2021
DOI: 10.3389/fpubh.2021.646770
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the Progression of Myopia in Children and Adolescents in Chongqing During COVID-19 Pandemic

Abstract: Background: The Covid-19 pandemic restricts children and adolescents from doing normal daily activities such as playing outdoors and going to school. The incidence and prevalence of myopia have increased during the COVID-19 pandemic. The aim of this study was to investigate and evaluate the impact of the home confinement during the COVID-19 pandemic on the progression of myopia among children and adolescents in Chongqing, China.Methods: The survey was conducted by using stratified samplings. Samples were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
105
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(115 citation statements)
references
References 41 publications
6
105
2
2
Order By: Relevance
“…2 It is reasonable to expect that these measures led to an increase in near work activities for children (digital or otherwise) and substantially less time spent outdoors. 3 , 4 , 5 Generally, time spent on near work is positively correlated with myopia progression, whereas time spent outdoors is negatively correlated with myopia. 6 , 7 , 8 , 9 , 10 Overall, during the periods of lockdown, children spent most of their time at home—that is, their refractive development was overwhelmingly determined by their domestic living environment.…”
Section: Introductionmentioning
confidence: 99%
“…2 It is reasonable to expect that these measures led to an increase in near work activities for children (digital or otherwise) and substantially less time spent outdoors. 3 , 4 , 5 Generally, time spent on near work is positively correlated with myopia progression, whereas time spent outdoors is negatively correlated with myopia. 6 , 7 , 8 , 9 , 10 Overall, during the periods of lockdown, children spent most of their time at home—that is, their refractive development was overwhelmingly determined by their domestic living environment.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that when children are out of school, they are physically less active, have much longer screen time, irregular sleep patterns, and have less favorable diets, resulting in weight gain and a loss of cardiorespiratory fitness ( 14 , 15 ). At the same time, some evidence support that the increased e-learning by digital screens and reduction in outdoor activities are two likely channels posing adverse risks for myopia development ( 16 ). In most countries it is projected that medium to long-term social distancing measures may curtail outdoor activities, leading to the undesirable effect of more time spent indoors on recreational digital screen time.…”
Section: Introductionmentioning
confidence: 99%
“…Articles have been published recently to investigate and evaluate the impact of home confinement on the progression of myopia among students in China ( 18 , 19 ). One survey was conducted by enrolling 1,733 and 1,728 students in 2020 and 2019 in Chongqing, respectively ( 16 ). It found that the percentage of myopic students increased by 10.40% during the COVID-19 ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased digital screen time and the overall time spent on near work, together with the decreasing outdoor time, increased the risk of myopia progression in students ( 6 ). Accelerated myopic progression has been reported during the COVID-19 pandemic ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%